(untitled) (Journal of Universal Science Research, 2023)
Music has been found to have positive effects on language learning, as it engages learners in listening, comprehension, and pronunciation. This article will examine the benefits of using songs as a tool for learning a foreign language and review some of the research studies that support this method.